Unsolved challenges in pediatric whole-exome sequencing: A literature analysis. (17th February 2017) - Bertier, Gabrielle; Sénécal, Karine; Borry, Pascal; Vears, Danya F.
Abstract: Whole-exome sequencing (WES) has been instrumental in the discovery of novel genes and mechanisms causing Mendelian diseases. While this technology is now being successfully applied in a number of clinics, particularly to diagnose patients with rare diseases, it also raises a number of ethical, legal and social issues. In order to identify what challenges were directly foreseen by technology users, we performed a systematic review of the literature. In this paper, we focus on recent publications related to the use of WES in the pediatric context and analyze the most prominent challenges raised by technology users. This is particularly relevant considering that a) most patients currently undergoing testing using WES to identify the genetic basis for rare diseases are children and b) their lack of capacity to consent for themselves makes them a vulnerable population and generates the need for specific ethical, legal and regulatory procedures. We identified key challenges that related to four main categories: (1) intake; (2) sequence production and analysis; (3) reporting of results and counseling considerations and (4) collaborative data interpretation and data sharing. We then contextualize these challenges in light of the recent recommendations and guidelines, published by professional societies that have significant potential to impact the field.